Hot diodes!: Dirt cheap cooking and electricity for the global poor?. (2019) - Gius, Grace; Walker, Matthew; Li, Andre; Adams, Nicholas J.; Van Buskirk, Robert; Schwartz, Pete
Abstract: Direct DC Solar (DDS) electricity can inexpensively cook food and charge appliances. Insulating the cooking chamber allows the food to cook with a lower-power (less expensive) solar panel over a longer cooking time. We explain how using a chain of diodes instead of a resistive heater extracts more energy from a solar panel over a variety of solar intensities and also acts as a rough, inexpensive voltage regulator to charge batteries and power appliances. We show how a diode heater produces more heat from a solar panel than either a DDS resistive heater or a PWM/battery-connected resistive heater, averaged over a wide variety of solar intensities. The resulting cost of electricity is already cost competitive with biomass cooking in many areas. Benefits include inexpensive access to electricity as well as reductions in indoor air pollution, deforestation, and cost/burden of providing cooking fuel. With continued decrease in the price of solar panels, DDS will become ever more effective for bringing electricity and electrical cooking to the global poor.